2016
DOI: 10.4103/2321-0656.164793
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of Vitamin D deficiency during pregnancy: A social health problem in India

Abstract: Background: Vitamin D deficiency (VDD) is an important public health problem and is implicated as a risk factor for glucose intolerance during pregnancy. We studied the prevalence of VDD in patients with gestational diabetes mellitus (GDM) and type 2 diabetes mellitus (T2DM). Materials and Methods: All GDM and T2DM patients evaluated between October and December 2014 were included in this cross-sectional, observational study. Patients with the use of vitamin D, glucocorticoids, and secondary diabetes were excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Our data showed the presence of VDD in a majority of the study participants. Previous studies have shown that VDD is a common problem in Indian women [ 19 ]. The literature is conflicting about the role of 25OHD in GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed the presence of VDD in a majority of the study participants. Previous studies have shown that VDD is a common problem in Indian women [ 19 ]. The literature is conflicting about the role of 25OHD in GDM.…”
Section: Discussionmentioning
confidence: 99%